Effects of light intensity on physiological traits of bamboo (Fargesia denudata) and poplar (Populus cathayana) during leaf senescence - QIAO Yun-zhou; LIU Meng-yu; WANG Kai-yun; ZHANG Yuan-bin (浙江大学学报. 农业与生命科学版, 2008)
To determine the effects of intensive light environment in subalpine region, Western China, on plant physiological traits during leaf senescence in late growth season, the photosynthetic rates, contents of photosynthetic pigments and soluble proteins of bamboo (Fargesia denudata) and poplar (Populus cathayana) leaves were investigated with a light shading of (30±2.5)%. Contents of malondialdehyde (MDA), activities of superoxide dismutase (SOD) and catalase (CAT) were also determined. The results show that, leaf photosynthetic rate, contents of soluble protein and photosynthetic pigments increased with the decrease of light intensity. The activities of SOD and CAT increased and the content of MDA decreased. These results suggested that moderate shading is beneficial to delay leaf senescence and to maintain high photosynthetic rate. Additionally, leaf photosynthetic rates, contents of soluble protein and photosynthetic pigments, activities of SOD and CAT of poplar were all higher than that of bamboo. This indicated that physiological indices relevant to leaf senescence are dependant on plant species. Bamboo and poplar are two of the most important species in dark coniferous forest of Western China, therefore, the specific differences in response to light intensities might impose remarkable effect on their ecologic niche and the succession process of forest stand.